Assessing Cochlear Implant Insertion Angle From an Intraoperative X-ray Using a Rotating 3D Helical Scala Tympani Model. Issue 6 (July 2020) - Giardina, Christopher K.; Canfarotta, Michael W.; Thompson, Nicholas J.; Fitzpatrick, Douglas C.; Hodge, Sarah E.; Baker, Jenna; O'Connell, Brendan P.
Abstract : Background: Angular insertion depth (AID) of the electrode array provides valuable information regarding intracochlear positioning, which can be used to predict outcomes and optimize performance. While computed tomography (CT) offers high-resolution imaging, there is a need to develop technology to accurately determine AID from intraoperative x-rays acquired at unknown angles. Methods: An algorithm was developed using a three-dimensional model of the scala tympani to estimate AID from an x-ray acquired at an unknown angle. The model is manipulated over the x-ray until the projection angle is inferred and the location of the round window and individual electrode contacts are identified. Validation of the algorithm involved 1) assessing accuracy with deviation from cochlear view by comparing AID determined with simulated x-rays to those determined with CT in a temporal bone model, and 2) assessing reproducibility in the clinical setting, by comparing intra- and inter-rater reliability with intraoperative x-ray in cochlear implant (CI) recipients, which were subsequently compared to AID determined with postoperative CT. Results: Estimates of AID from x-rays were generally within 10 degrees of CT regardless of deviation from cochlear view. Excluding two outliers with poor imaging quality, the intraclass correlation coefficients for intra- and inter-rater reliability were excellent (0.991 and 0.980, respectively). Conclusion: With intraoperative x-rays of sufficient quality, the helical scala tympani model can be used to accurately and reliably determine AID without the need to specify a preferred image angle. The application can therefore be used in most CI recipients when a postoperative CT is not available.